Challenges of Writing Research Articles in English for University-Level EFL Teachers - Tiwari, Hari Prasad (Universitas Islam Negeri Walisongo Semarang, 2023)
Writing research articles in English is a challenging task for non-native speakers of English, as it requires linguistic competence, rhetorical awareness, disciplinary knowledge, and familiarity with the research writing conventions. The qualitative study explores English non-native speakers' challenges while writing research articles (RAs) in English. The participants were 12 university-level English as a Foreign Language (EFL) teachers selected using snowball sampling. The data was collected using semi-structured interviews and analyzed using a thematic approach. The findings revealed four challenges: linguistic, rhetorical, disciplinary, and cultural. Linguistic challenges affect the clarity and credibility of the writing. In contrast, rhetorical challenges involve following the conventions, arguments, and citations of RAs in English. Disciplinary challenges require adapting to the norms and practices of different fields of study, and cultural challenges reflect the preferences for directness, formality, and objectivity in writing. The study shows the complexity and interrelatedness of these challenges and suggests a flexible and nuanced approach to overcome them.